Differentiation of Recurrent Tumor and Posttreatment Changes in Head and Neck Squamous Cell Carcinoma: Application of High b-Value Diffusion-Weighted Imaging - Hwang, I. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: High b-value DWI has been expected to have an additional diagnostic role and demonstrated some promising results in head and neck cancer. The aim of this study was to evaluate the diagnostic performance of DWI at a high b-value (b=2000 s/mm(2)) compared with a standard b-value (b=1000 s/mm(2)) and the ratio of ADC values of high and standard b-values for their ability to differentiate between recurrent tumor and posttreatment changes after the treatment of head and neck squamous cell carcinoma. MATERIALS AND METHODS: A total of 33 patients diagnosed with head and neck squamous cell carcinoma were enrolled in the present study; all had contrast-enhancing lesions on follow-up MR imaging. All patients underwent single-shot echo-planar DWI at b=1000 s/mm(2) and b=2000 s/mm(2), and corresponding ADC maps were generated (ADC(1000) and ADC(2000), respectively). The mean ADC(1000), ADC(2000), and ADC(ratio) (ADC(ratio) = ADC(2000)/ADC(1000) × 100) values were evaluated within a manually placed ROI with contrast-enhanced T1-weighted images as references. For the statistical analysis, we performed a Student t test and multivariate logistic regression. RESULTS: The mean ADC(1000) in recurrent tumor was significantly lower than that in posttreatment changes (P < .001), whereas the mean ADC(2000) resulted in no significant difference (P = .365). The mean ADC(ratio) was significantly higher in recurrent tumor than that in posttreatment changes (73.5 ± 7.2% vs 56.9 ± 8.8%, respectively; P < .001). Multivariate logistic regression analysis revealed that the ADC(ratio) was the only independently differentiating variable (P = .024). The sensitivity, specificity, and accuracy of ADC(ratio) were 95.0%, 69.2%, and 84.8%, respectively, by use of the optimal cutoff value of 62.6%. CONCLUSIONS: We suggest that the ADC(ratio) calculated from the ADC(1000) and ADC(2000) is a promising value for the differentiation of recurrent tumor and posttreatment changes in head and neck squamous cell carcinoma.